2013
DOI: 10.1371/journal.pone.0076857
|View full text |Cite
|
Sign up to set email alerts
|

UV-Light Effects on Cytochrome C Modulated by the Aggregation State of Phenothiazines

Abstract: The present study shows the factors that modulate the photodamage promoted by phenothiazines. Cytochrome c was irradiated with UV light for 120 min, over a pH range from 4.0 to 8.0, in the absence and in the presence of different concentrations of thioridazine (TR) and fluphenazine (FP). In the absence of phenothiazines, the maximal rate of a Soret band blue shift (nm/min) from 409 to 406 nm was obtained at pH 4.0 (0.028 nm/min). The presence of phenothiazines at the concentration range 10-25 µmol/L amplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The photodegradation of CIPRO in the absence of another photosensitization indicated that CIPRO was the source and target of the reactive species. Normally, organic photosensitizers such as methylene blue 50 , phenothiazines 51 and porphyrins 52 produce electronically excited species by mechanisms type II and I. Mechanism type II consists of the transfer of electronic excitation energy from the photosensitizer to molecular oxygen, generating singlet molecular oxygen O 2 ( 1 Δ g ), a highly reactive species.…”
Section: Resultsmentioning
confidence: 99%
“…The photodegradation of CIPRO in the absence of another photosensitization indicated that CIPRO was the source and target of the reactive species. Normally, organic photosensitizers such as methylene blue 50 , phenothiazines 51 and porphyrins 52 produce electronically excited species by mechanisms type II and I. Mechanism type II consists of the transfer of electronic excitation energy from the photosensitizer to molecular oxygen, generating singlet molecular oxygen O 2 ( 1 Δ g ), a highly reactive species.…”
Section: Resultsmentioning
confidence: 99%
“…These cation radicals are supposed to be responsible for the pro-oxidant activity of phenothiazines. However, their stability may be limited by cellular events such as membrane association [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct continuous wave EPR of Cygb heme iron was measured as previously described for other hemeproteins with modifications [ 47 , 48 ]. The protein concentration was of 1.2 mmol.L -1 and when present, the peroxide concentration was of 12 mmol.L -1 .…”
Section: Methodsmentioning
confidence: 99%